Individuality matters for substrate-size preference in the Nile tilapia juveniles - Maia, Caroline Marques [UNESP]; Volpato, Gilson Luiz [UNESP] (Taylor & Francis, 2018)
Preference tests have usually been used to identify nonhuman animal preferences for welfare purposes (environmental enrichment), but they are mostly at the group level—that is, group preferences for resources or environmental conditions. However, a more robust method was developed to analyze animal preference, and this method detected clear individual variation in preferences of Nile tilapia fish (Oreochromis niloticus) selecting different background colors. Here, a clear individual variability of preference was found for another type of enrichment—the sizes of substrate. Despite this variability, a consistent response was detected at the group level: Small gravel was less frequently preferred than avoided, and the more decided fish (those who preferred only one substrate size) never preferred gravel over sand-size substrate. That is, Nile tilapia avoided gravel and preferred smaller substrate, and this finding was possibly associated with their mouth gap. Considering that small gravel is a substrate often used for fish rearing, these findings highlight fish keepers’ incorrect perception of fish needs, based mostly on arbitrary criteria instead of actual fish preferences and without considering individual needs.
Keywords: gravel; individual variability; Preferred options; sand